Efektivitas Topikal Aplikasi Fluoride Menggunakan Ekstrak Teh Hijau Dibandingkan dengan Sodium Fluoride Pada Gigi Sapi - Ekky Berliana R P; Istien Wardani; Eriza Juniar (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Prevention of caries and periodontal disease by performing dental health improvement has become a major destination in the world of dentistry. Topical application of fluoride is one of the most effective ways to prevent caries, fluoride inhibits the absorption of salivary proteins on the surface of the email so the pellicle and plaque formation reduced,increase enamel remineralization, resistance to acids and decreased pH. Topical application of fluoride commonly used is sodium fluoride 0.1%. Green tea (Camellia sinensis) can be an alternative herbs as a topical application of fluoride because it has reduced the growth of plaque and have antibacterial. Purpose: To determine the effectiveness of topical fluoride applications using green tea extract compared to sodium fluoride on the teeth cow. Materials and Methods: This study was true experimental laboratories with post test only control group design. The subjects in this study was a teeth cow (Bovine) is applied with the topical application of fluoride, control group without administration of topical application offluoride, treatment group one with Sodium fluoride 0.1%, and the treatment group two with green tea extract (Camellia sinensis) 0.1%. Counting the amount of fluoride by Energy Dispersive X-ray Spectrophotomrtry (EDS). The data was processed by Levene test and one way ANOVA. Result: There are no significant differences in the number of fluoride among all groups (P> 0.05). Conclusion: There were no significant differences in the effectiveness of topical application of fluoride using green tea extract (Camellia sinensis) concentration of 0.1% compared with 0.1% Sodium fluoride on teeth cow (Bovine.